The Influence of Entrepreneurial Orientation, Artistic Orientation and Financial Literacy on Business Performance Creative UKM Players in Bandar Lampung: Pengaruh Orientasi Kewirausahaan, Orientasi Artistik dan Literasi Keuangan Terhadap Kinerja Usaha Pelaku UKM Kreatif di Bandar Lampung - Septiani, Anggi (Jurnal Kompetitif Bisnis, 2021)
The Influence of Entrepreneurial Orientation, Artistic Orientation and Financial Literacy on Business Performance Creative UKM Players in Bandar Lampung Anggi Septiani1, Suripto2, M. Iqbal Harori3 Jurusan Ilmu Administrasi Bisnis FISIP, Universitas Lampung Korespondensi: septianianggi6@gmail.com Abstract This study aims to determine influence between entrepreneurial orientation, artistic orientation, and financial literacy on business performance. Respondents in this study were creative UKM players in Bandar Lampung. This type of research is an explanatory study using a quantitative approach. The population in this study were Creative UKM players registered at the Cooperative and UMKM Office. The number of samples of 30 respondents based on purposive sampling technique. This research was tested using multiple linear regression test with analysis tool SPSS 24 program. The results showed that partially there is an influence between entrepreneurial orientation, artistic orientation, and financial literacy with significant values ​​of 0.029, 0.009, and 0.004. Furthermore, simultaneously it shows that there is an influence between entrepreneurial orientation, artistic orientation, and financial literacy on business performance with a value of Sig 0.000. Keywords: Entrepreneurship Orientation, Artistic Orientation, Financial Literacy and Business Performance